A new class of human CpG Island promoters with primate-specific repeats - K. Naga Mohan; Anuhya Anne; Lov Kumar; J. Richard Chaillet (Scientific Reports)
Abstract A subset of imprinting control regions (ICRs) in the human and mouse possess CpG islands associated with imperfect tandem repeats (TRs) that were shown to be essential for genomic imprinting through genetic studies. To identify whether this feature is also present in non-imprinted CpG island promoters, we performed extensive dot plot analyses and identified 342 (326 autosomal and 16 X-chromosomal) human CpG island gene promoters associated with imperfect TRs of ≥ 400 bp, unit lengths 50–150 bp. Most occur as clusters at the human chromosome ends, distinct from the clusters of imprinted genes, and enriched in neurodevelopmental/behavioral disorders, with some showing interindividual variation in methylation levels. A subset of TR-CGIs is highly methylated and remains so during reprogramming to primed iPSCs, but become unmethylated in naïve iPSCs, as in the case of ICRs. Transcript levels correlate with methylation levels for some TR-CGI genes suggesting their gene regulatory potential. Non-TR CGI mouse orthologs of methylated human TR-CGIs are unmethylated in mouse, suggesting the association of TRs with higher methylation levels. Most human TR-CGIs accompanied primate evolution after divergence from mouse TR-CGIs with evidence of recent additions in hominid evolution. In summary, the incorporation of TRs in certain CGI promoters in mammalian evolution results in the unique ability to acquire methylation during human embryonic development and resist reprogramming to a pluripotent stem cell state with an effect on gene expression.